"Die Young": On Pop Music, Social Violence, Self-Censorship, and Apology Rituals. Issue 3 (27th May 2017) - Carpenter, Alexander
Abstract: This article examines the response of musicians to social violence, focusing specifically on the phenomenon of hybridized corporate/self-censorship by pop musicians in the wake of the Sandy Hook school shooting in Newtown, Connecticut, at the end of 2012. Immediately following the shooting, several popular songs with putatively inflammatory titles and lyrics—most notably, Keha's "Die Young" and Foster the People's "Pumped Up Kicks"—were pulled from the airwaves, largely in the name of a generalized sensitivity to the emotional needs of the listening public. This action received the vociferous support of the artists themselves, who issued concomitant pro forma apologies for their work. The tacit acknowledgment of the connections between music and acts of violence, the complicity of artists in the censorship or suppression of their own work, and their a posteriori participation in apology rituals are the focus here, with comparisons also drawn between similar acts of social violence—the Columbine school shooting of 1999 in particular—and the calls for and responses to the music censorship that followed.